SoulStirrers : Black Art and the Neo-Ancestral Impulse - Newsum, H. E., 1951- (University Press of Mississippi, 2016)
In SoulStirrers, H. Ike Okafor-Newsum describes the birth and development of an artistic movement in Cincinnati, Ohio, identified with the Neo-Ancestral impulse. The Neo-Ancestral impulse emerges as an extension of the Harlem Renaissance, the Negritude Movement, and the Black Arts Movement, all of which sought to re-represent the'primitive'and'savage'black and African in new terms. Central to the dominant racial framework has always been the conception that the black subject was not only inferior, but indeed incapable of producing art. The Neo-Ancestral impulse posed a challenge to both existing form and content. Like its intellectual antecedents, the movement did not separate art from life and raised a central question, one that the'soul stirrers'of Cincinnati are engaging in their artistic productions. Okafor-Newsum defines collapsing of the sacred and the profane as a central tendency of African aesthetics, transformed and rearticulated here in the Americas. In this volume, the artistic productions ask readers to consider the role of those creating and viewing this art by attempting to shift the way in which we view the ordinary. The works of these artists, therefore, are not only about the survival of African-derived cultural forms, though such remains a central effect of them. These extraordinary pieces, installations, and movements consistently refer to the cultural reality of the Americas and the need for political and intellectual transformation. They constitute important intellectual interventions that serve as indispensable elements in the redefinition and reinterpretation of our society. Featuring numerous color illustrations and profiles of artists, this volume reveals exciting trends in African American art and in the African diaspora more broadly.